Correlations of special endurance and peak force tests in the water and on the land of qualified swimmers - Volkova, E.; Solovjova, J.; Zuoziene, I.; Brazaitis, M. (LASE Journal of Sport Science, 2010)
In order to achieve high results in swimming it is important to pay a lot of attention to physical qualities, absence of which might limit the growth of the results. The use of tests allows controlling sportsmen's functional condition, as well as determining different levels of endurance and force and its sufficiency. The aim of our work is to optimize the management of swimmers' training process on the basis of special testing results. In experiment were involved 11 Lithuanian junior national team swimmers (age 18±3, height 183±4 cm, weight 75±9 kg, BMI (body mass index) 22±2). In two weeks we accomplished special endurance tests in pool: 2x25m with 80s interval, 4x50m with 45s interval, 4x50m with 10s interval, 8x50 with 10s interval. Force tests consisted of pulling force in water swimming only with hands, swimming only with legs, swimming with full coordination, swimming in 30 second and fixed force endurance index. We have measured isometric torque, maximal force moment, and maximal force moment at muscle stimulation (20 Hz/s, 100Hz/250ms, 100Hz/s), force moment at the angular velocity of 30, 90, 180 degrees per second of curved and straighten upper shank and thigh extensor muscles was measured using an isokinetic dynamometer (System 3; Biodex Medical Systems, Shiley, New York). After the tests we calculated group average results and made correlative analysis and estimation of swimmers' results.